Both degradation and AOX accumulation are significantly enhanced in UV/peroxymonosulfate/4-chlorophenol/Cl− system: two sides of the same coin?. Issue 20 (21st February 2017) - Wang, Zhaohui; Feng, Min; Fang, Changling; Huang, Ying; Ai, Luoyan; Yang, Fei; Xue, Ying; Liu, Wenqian; Liu, Jianshe
Abstract : External chloride ion may lead to AOX accumulation in UV/PMS process, although 4-CP degradation was accelerated. Abstract : The presence of external chloride can lead to a 47-fold increment in degradation rates of 4-chlorophenol than those in the absence of chloride in UV/peroxymonosulfate process. The other side of the same coin is an undesirable accumulation and increase in absorbable organic halogen (AOX) was observed in the presence of chloride, with formation of some more toxic tetrachlorinated byproducts.